Inhibitor development in haemophilia according to concentrate - Fischer, Kathelijn; Lassila, Riita; Peyvandi, Flora; Calizzani, Gabriele; Gatt, Alex; Lambert, Thierry; Windyga, Jerzy; Iorio, Alfonso; Gilman, Estelle; Makris, Michael (Thrombosis and Haemostasis, 2015)
Inhibitor development represents the most serious side effect of haemophilia treatment. Any difference in risk of inhibitor formation depending on the product used might be of clinical relevance. It was this study’s objective to assess inhibitor development according to clotting factor concentrate in severe haemophilia A and B. The European Haemophilia Safety Surveillance (EUHASS) was set up as a study monitoring adverse events overall and according to concentrate. Since October 2008, inhibitors were reported at least quarterly. Number of treated patients was reported annually, specifying the number of patients completing 50 exposure days (Previously Untreated Patients, PUPs) without inhibitor development. Cumulative incidence, incidence rates and 95 % confidence intervals (CI) were calculated. Data from October 1, 2008 to December 31, 2012 were analysed for 68 centres that validated their data. Inhibitors developed in 108/417 (26 %; CI 22–30 %) PUPs with severe haemophilia A and 5/72 (7 %; CI 2–16%) PUPs with severe haemophilia B. For Previously Treated Patients (PTPs), 26 inhibitors developed in 17,667 treatment years [0.15/100 treatment years; CI 0.10–0.22) for severe haemophilia A and 1/2836 (0.04/100; (CI 0.00–0.20) for severe haemophilia B. Differences between plasma-derived and recombinant concentrates, or among the different recombinant FVIII concentrates were investigated. In conclusion, while confirming the expected rates of inhibitors in PUPs and PTPs, no class or brand related differences were observed.
Keywords: Adverse Drug Reaction Reporting Systems; antibodies; neutralising; factor VIII; haemophilia A; haemophilia B